Engineering spherical lead zirconate titanate to explore the essence of piezo-catalysis. (October 2017) - Feng, Yawei; Ling, Lili; Wang, Yanxu; Xu, Zhenmin; Cao, Fenglei; Li, Hexing; Bian, Zhenfeng
Abstract: Piezo-catalysis induced by piezoelectric polarization has been proven to be a powerful technology for potential applications in the energy and environment. It is generally accepted that piezo-catalysis derived the easily deformation from the piezoelectric materials with one or two dimensions. In this study, piezoelectric materials lead zirconate titanate (PZT) with a spherical morphology was synthesized, which is used to explore whether the widely accepted principle that is one or two-dimensional structure is necessary in the piezo-catalysis process is exclusive. We would like to clarify the relationship between deformation and piezoelectric catalytic performance. In addition, a key fundamental problem that has not yet been fully solved whether the charges of the reaction are from polarized charges or free charges. We investigate the role of polarization charges and free charges in piezoelectric catalysis by doping the piezoelectric material. It is hoped that the study of this work will re-understand and explain the mechanism of piezoelectric catalytic reaction. Graphical abstract: Highlights: The piezoelectricity of PZT is important than the morphology during piezo-catalysis. The free charges in PZT produce oxidized active species on piezoelectric material. Active species decompose dye molecules into carbon dioxide and water.